2014
DOI: 10.1371/journal.pone.0095754
|View full text |Cite
|
Sign up to set email alerts
|

Late Miocene–Pliocene Paleoclimatic Evolution Documented by Terrestrial Mollusk Populations in the Western Chinese Loess Plateau

Abstract: The Neogene eolian deposits in the Chinese Loess Plateau (CLP) are one of the most useful continental deposits for understanding climatic changes. To decipher Late Neogene paleoclimatic changes in the CLP, we present a terrestrial mollusk record spanning the time interval between 7.1 and 3.5 Ma from the western CLP. The results indicate four stages of paleoclimatic evolution: From 7.1 to 6.2 Ma, cold and dry climatic conditions prevailed as evidenced by high values of the total number of cold-aridiphilous (CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…B. claimed a relatively strong winter monsoon in the Late Miocene. A winter monsoon dominated climate over the western Loess Plateau before 6 Ma is also reported by Li et al (2008Li et al ( , 2014, who use cold-philous species of fossil snails as an indicator for the winter monsoon strength. A recent model study using the ensemble of Mid-Pliocene global simulations also revealed a stronger-than-present winter monsoon wind in southern China and India (Zhang et al, 2013).This further supports the existence of a strong winter monsoon in the pre-Quaternary periods when the global climate was generally warmer.…”
Section: Strong Winter Monsoon Wind In the Late Miocenesupporting
confidence: 63%
See 3 more Smart Citations
“…B. claimed a relatively strong winter monsoon in the Late Miocene. A winter monsoon dominated climate over the western Loess Plateau before 6 Ma is also reported by Li et al (2008Li et al ( , 2014, who use cold-philous species of fossil snails as an indicator for the winter monsoon strength. A recent model study using the ensemble of Mid-Pliocene global simulations also revealed a stronger-than-present winter monsoon wind in southern China and India (Zhang et al, 2013).This further supports the existence of a strong winter monsoon in the pre-Quaternary periods when the global climate was generally warmer.…”
Section: Strong Winter Monsoon Wind In the Late Miocenesupporting
confidence: 63%
“…Recent model studies have revealed that different parts of the Asian orography have distinct influence on the Siberian High and the westerly jet stream and therefore the winter monsoon (Shi et al, 2014;Zhang et al, 2014). Zhang et al (2014) showed that the presence of the middle TP can enhance the Siberian High but reduce the winter monsoon wind in East China (Fig.…”
Section: Strong Winter Monsoon Wind In the Late Miocenementioning
confidence: 99%
See 2 more Smart Citations
“…The Miocene climate was slightly warmer and wetter and spawned the monsoon system which has affected Asian vegetation [ 97 99 ]. After the late Miocene, the climate gradually cooled and became arid [ 100 , 101 ]. The late-Miocene-to-Pliocene climate change accelerated the diversification of insular species [ 102 105 ], which may be partly due to sea-level fluctuations accompanying disjunction and connection between continents and islands [ 106 ].…”
Section: Discussionmentioning
confidence: 99%